2014
DOI: 10.1097/qai.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Cancer in Italian Persons With AIDS, 1986–2005

Abstract: The persisting, although narrowing, gap in cancer survival between PWA and non-PWA indicates the necessity of enhancing therapeutic approaches, so that PWA can be provided the same chances of survival observed in the general population, and improving cancer prevention and screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
(58 reference statements)
2
17
0
1
Order By: Relevance
“…Our study is consistent with prior studies finding reduced survival among HIV-infected individuals diagnosed with lung and prostate cancers, (13,14,16,17) with several finding increased mortality independent of disease stage at diagnosis. (16,17) Among injection drug users, Shiels et al found a nearly four-fold higher risk of death after diagnosis with lung cancer among HIV-infected compared with HIV-uninfected individuals after adjustment for SEER summary stage and smoking, although with 29 cases this did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study is consistent with prior studies finding reduced survival among HIV-infected individuals diagnosed with lung and prostate cancers, (13,14,16,17) with several finding increased mortality independent of disease stage at diagnosis. (16,17) Among injection drug users, Shiels et al found a nearly four-fold higher risk of death after diagnosis with lung cancer among HIV-infected compared with HIV-uninfected individuals after adjustment for SEER summary stage and smoking, although with 29 cases this did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 93%
“…Of studies comparing cancer prognosis by HIV status, HIV infection has been associated with increased mortality from multiple NADCs, including HL (1315) and lung, (13,14,16,17) colorectal, (13,14) anal, (14,18) and prostate (14) cancers. However, while mortality from AIDS and other causes may result in reduced survival for HIV-infected individuals, few studies have examined cancer-specific mortality (16); furthermore, several were conducted among individuals living with AIDS, (13,14) who are at particularly high risk of death from non-cancer causes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved survival observed here after diagnosis of hematological malignancies was not explained by changes in the characteristics of HIV‐infected individuals over time but rather by a calendar‐period effect, likely related to more often use of the same cancer treatment protocols as in HIV‐uninfected individuals and to a better adherence to these protocols because of better tolerability. Despite the clear trend towards improved survival after hematological malignancies, we observed a marked difference between the HIV‐infected and general populations for cases diagnosed in 2001–2004 even when restricting to DLBCL, confirming the results of previous studies . Although the improvement in survival could be related to better access to cancer treatment over time, suboptimal management of HIV‐infected individuals with cancer likely persists in 2001–2004; indeed, HIV‐seropositive cancer patients do not receive the same number of cycles or the same doses of chemotherapy as patients not infected by HIV .…”
Section: Discussionsupporting
confidence: 84%
“…The Italian Cancer and AIDS registries linkage study found much lower 5‐year survival probabilities than ART‐CC after several specific cancers, for example, liver cancer 8% vs . 26%, but our study was during the early ART period and included PLHIV not on ART who had an AIDS diagnosis . Another Italian study which included PLHIV not on ART found similar 5‐year survival to ART‐CC after a diagnosis of Hodgkin's lymphoma .…”
Section: Discussionmentioning
confidence: 82%